Peak flow variation in childhood asthma: correlation with symptoms, airways obstruction, and hyperresponsiveness during long term treatment with inhaled corticosteroids. Issue 2 (1st February 1999) - Brand, Paul L P; Duiverman, Eric J; Waalkens, Herman J; van Essen-Zandvliet, Elisabeth E M; Kerrebijn, Karel F; ,
Abstract : BACKGROUND: Guidelines for asthma management focus on treatment with inhaled corticosteroids and on home recording of peak expiratory flow (PEF). The effect of maintenance treatment with inhaled corticosteroids on PEF variation and its relation to other parameters of disease activity were examined in 102 asthmatic children aged 7–14 years. METHODS: During 20 months of treatment with inhaled salbutamol, with or without inhaled budesonide (600 μg daily), forced expiratory volume in one second (FEV1 ), the dose of histamine required to provoke a fall in FEV1 of more than 20% (PD20 ), the percentage of symptom free days, and PEF variation were assessed bimonthly. PEF variation was computed as the lowest PEF as a percentage of the highest PEF occurring over 14 days, the usual way of expressing PEF variation in asthma self-management plans. For each patient using inhaled corticosteroids within subject correlation coefficients (ρ) were computed of PEF variation to the percentage of symptom free days, FEV1, and PD20 . RESULTS: PEF variation decreased significantly during the first two months of treatment with inhaled corticosteroids and then remained stable. The same pattern was observed for symptoms and FEV1 . In contrast, PD20 histamine continued to improve throughout the whole follow up period. In individual patients predominantly positive associations of PEF variation with symptoms, FEV1, and PD20 were found, but the ranges of these associations were wide. CONCLUSIONS: During treatment with inhaled corticosteroids the changes in PEF variation over time show poor concordance with changes in other parameters of asthma severity. When only PEF is monitored, clinically relevant deteriorations in symptoms, FEV1, or PD20 may be missed. This suggests that home recording of PEF alone may not be sufficient to monitor asthma severity reliably in children.